The Relationship of Job Stress with Employee Job Satisfaction in the Company and its Implications for Guidance and Counseling Services - Estelita Mahardikawati; Mursyid Ridha (Jurnal Neo Konseling, 2019)
This research is motivated by the phenomenon of the many employees who complain becouse of the demands of the work they live. Problems that arise in the work environment have a profound effect on employees. Complaints in the form of physical  disorders are often experienced by employees. There are also employees who choose to stop working after working for less than one month, due to heavy workload. Job satisfaction is an individual’s way of feeling his work resulting from the individual’s attitude toward various aspects contained in the job. One factor that affects job satisfaction is job stress. This research is a descriptive correlational type of research with quantitative methods. As for the subjects in this study were all employees of the Auto 2000 Service field at Laweh in Banu Hampu sub-district, Bukittinggi, which amounted to 12 employees. The research instrument used was a job stress questionnaire and a job satisfaction questionnaire. Data were analyzed with descriptive statistical techniques and Pearson Product Moment techniques with the help of the SPSS For Windows 20.0 program. The results revealed that (1) employee job stress was in the low category, (2) employee job satisfaction was in the high category and (3) there was a significant negative relationship between job stress and employee job satisfaction with a correlation coefficient of -0,635 which was at the significance level 0.027. Based on the research findings, it is suggested to counselors to be able to provide several service areas in the industrial business world such as job placement, job adjustments, job satisfaction, job transfer and other problem alleviation, in order to help to alleviate job stress and increase employee job satisfaction in the company.